The Effect of Compensation on Teacher Performance at Muhammadiyah Elementary School 12 Pamulang - Maya Dwi Febrianti; Bambang Irawan (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine the effect of compensation on teacher performance at Muhammadiyah 12 Elementary School, Pamulang. This study aims to determine the extent of compensation's influence on teacher performance at Muhammadiyah 12 Elementary School, Pamulang. This quantitative study used a questionnaire as the data collection method. The sampling technique used a census or total sampling of 65 respondents. The data analysis method used simple linear regression analysis with IBM SPSS 29. The results of this study indicate that compensation has an effect on teacher performance. This is evidenced by the results of the simple linear regression analysis, which yielded a figure of 51.3% and the remaining 48.7%. If the compensation received is in accordance with the job description, teacher performance will improve, and conversely, if the compensation is not in accordance, teacher performance will decline. The magnitude of the effect of compensation on teacher performance is 51.3%. This is evidenced by the results of the coefficient of determination.